2016
DOI: 10.4172/2155-9546.1000415
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Dietary Carbohydrate/Lipid Ratios on Growth, Feed Utilization and Body Composition of Early Giant Grouper Epinephelus Lanceolatus Juveniles

Abstract: An 8-week growth trial was undertaken to determine effects of different dietary carbohydrate (CHO)/lipid (L) ratios on growth, feed utilization and body composition of early giant grouper Epinephelus lanceolatus juveniles. Five isoenergetic (4.1 kcal/g) and isonitrogenous (50% CP, dry-matter basis) experimental diets were formulated to contain different crude lipid (CL) levels (22%, 19.8%, 17.6%, 15.4% or 13.2%, dry-matter basis) and together different corn starch levels (0%, 4.95%, 9.9%, 14.85% or 19.8%), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
1
5
2
Order By: Relevance
“…The results of the present study were higher than those reported by some previous studies, such as studies on giant grouper (Li & Wu, 2016) and orange-spotted grouper (Wang, Han, et al, 2017).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…The results of the present study were higher than those reported by some previous studies, such as studies on giant grouper (Li & Wu, 2016) and orange-spotted grouper (Wang, Han, et al, 2017).…”
Section: Discussioncontrasting
confidence: 97%
“…The results of the giant grouper (Li & Wu, 2016) study used WGR as the evaluation index and corn starch as the CHO source, and the optimal CHO:L ratio was 1.30, corresponding to a dietary crude lipid content of 14.79% and a dietary CHO content of 19.23%. This result was much smaller than the results of this study, probably because the CHO sources used in the experiment were different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No effect of carbohydrate sources or levels were recorded on body contents of tilapia. Similar results were obtained in different species: tilapia [27,34] , trout [35] and grouper [3,36] . On the contrast, a positive increase in lipid contents by increase carbohydrate levels were recorded in other fish species such as trout (Salmo gairdneri) [26] and catfish (Clarias gareipinus) [37,38] .…”
Section: Discussionsupporting
confidence: 85%
“…Enough amount of carbohydrate would enhance growth performance and immunity [2,3,4] . Besides, carbohydrate of starch origin is crucial in improving feed physical quality with good binding and expansion properties [5] .…”
Section: Introductionmentioning
confidence: 99%